Study Of Employment Characteristics And Entrepreneur Competency As Effort To Increase SMEs Performance - Yudi Wahyudin Suwandi; Imas Komariyah (International Journal of Applied Business and International Management, 2023)
ABSTRACTÂ The purpose of this research is to focus on the study of job characteristics and competencies of SMEs as an effort to improve the performance of SMEs. Based on Law no. 20 of 2008, Micro, Small, and Medium Enterprises, Micro Enterprises are productive businesses owned by individuals and/or business entities that meet the criteria. a business that is not a subsidiary or not a branch of a company that is owned, controlled or becomes a part either directly or indirectly of a Medium or Large Business that meets the criteria of a Small Business. MSMEs are the most vital sector as a support for the regional economy in creating jobs. West Bandung Regency makes a major contribution to economic activities by continuing to increase the number of industries and SMEs that contribute to providing employment opportunities.This study uses a qualitative method, so what is taken from this explanatory research is its descriptive-holistic nature and the use of the theoretical basis used in the research framework. Thus, the authors hope to find the depth of interpretation of the data and test the theoretical criteria used in this study. The study that the researcher conducts The case study is one of the research methods that is carried out in-depth examination rather than generalizing to a situation or phenomenon called a case by using systematic methods of observing, collecting data, analyzing information, and reporting the results. As a result, you will get a deep understanding of why something happens and can be the basis for further research with a single case study, data collected through observation and in-depth interviews, and documentation to produce the best conclusions and can be an argument for researchers.The results of the study indicate that job characteristic and entrepreneurial competencies have not been able to fully support the improvement of SME performance. This is because the number of SMEs in West Bandung Regency is less developed there are still many of the products they offer the same, resulting in high competition among SMEs, and for buyers, there is no other choice. The results of the study can be concluded that the characteristics of work and entrepreneurial competence as an effort to improve the performance of SMEs have not been achieved, West Bandung SMEs need to be developed and managed properly and there is a cooperation between SMEs actors and the relevant government.